2020
DOI: 10.3389/fonc.2020.513874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enhanced Recovery After Surgery on Postoperative Recovery and Quality of Life in Patients Undergoing Laparoscopic Partial Nephrectomy

Abstract: Patients who underwent laparoscopic partial nephrectomy from the First Affiliated Hospital of Nanjing Medical University from May 2016 to May 2019 were randomly divided into enhanced recovery after surgery (ERAS) and control groups. The clinical indicators, preoperative and postoperative anxiety, depression, and postoperative quality of life were compared between the two groups. The recovery time, hospitalization cost, incidence of complications, and postoperative anxiety of patients in the ERAS group were low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…In this study, prophylactic anti-nausea drugs were provided to patients on a routine basis rather than the traditional demanding-prescription mode. The results indicated that the early incidence (postoperative 0-6 h) of nausea in the ERAS group was significantly lower, while the late incidence of PONV in the two groups showed no significant difference, which was consistent with previous studies [10]. We considered that these different results were partly because of the nature of retroperitoneal surgery; namely, the vasovagal reflex might be calmed in the first 6 h after surgery by anti-nausea drugs, while later with the return of patients' water intake and upcoming PONV pathophysiological climax (24 h postoperatively), cases of PONV occurred more often and intensively [19,20].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, prophylactic anti-nausea drugs were provided to patients on a routine basis rather than the traditional demanding-prescription mode. The results indicated that the early incidence (postoperative 0-6 h) of nausea in the ERAS group was significantly lower, while the late incidence of PONV in the two groups showed no significant difference, which was consistent with previous studies [10]. We considered that these different results were partly because of the nature of retroperitoneal surgery; namely, the vasovagal reflex might be calmed in the first 6 h after surgery by anti-nausea drugs, while later with the return of patients' water intake and upcoming PONV pathophysiological climax (24 h postoperatively), cases of PONV occurred more often and intensively [19,20].…”
Section: Discussionsupporting
confidence: 91%
“…We were initially surprised because the ERAS group should theoretically recover better and faster than the traditional group and therefore should have shorter postoperative LOS and lower hospital costs [4,7]. Through an in-depth literature study, we found that the medical expenses in our medical center were much lower than those extracted from other studies in the same country, either in the traditional group or the ERAS group [10,11]. Moreover, the LOS of both groups in our medical center was similar to that in the reported ERAS cohorts.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…ERAS can effectively shorten the lengths of time to first postoperative flatus and bowel movement, and improve the physical functions of patients [18,19]. However, ERAS combines a series of evidence-based perioperative optimization measures, including preoperative prehabilitation, early ambulation, early eating, and pain control.…”
Section: Introductionmentioning
confidence: 99%